2007
DOI: 10.1002/cne.21405
|View full text |Cite
|
Sign up to set email alerts
|

Functional connections within the human inferior frontal gyrus

Abstract: The highly convoluted and cytoarchitectonically diverse inferior frontal gyrus (IFG) of humans is known to be critically involved in a wide range of complex operations including speech and language processing. The neural circuitry that underlies these operations is not fully understood. We hypothesized that this neural circuitry includes functional connections within and between the three major IFG subgyri: the pars orbitalis, pars triangularis, and pars opercularis. To test this hypothesis we employed electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 54 publications
3
24
0
1
Order By: Relevance
“…We further note The inferior frontal gyrus, which includes Broca's area, is critically involved in speech production and language processing. 46 It is functionally connected with the temporal lobe to form a language network. Our findings of increased functional connectivity of the inferior frontal gyrus including Broca's area with temporal cortex and cingulate areas, and the correlation of increased functional connectivity with the positive/negative symptoms, implicate language-related frontal areas as key regions related to the onset of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…We further note The inferior frontal gyrus, which includes Broca's area, is critically involved in speech production and language processing. 46 It is functionally connected with the temporal lobe to form a language network. Our findings of increased functional connectivity of the inferior frontal gyrus including Broca's area with temporal cortex and cingulate areas, and the correlation of increased functional connectivity with the positive/negative symptoms, implicate language-related frontal areas as key regions related to the onset of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…The anterior and posterior cingulate gyri are mainly involved in supporting internally directed cognition, in modulation of emotional responses, and in attentional processing [31,32]. The pars opercularis is critical for speech and language functions [30,33].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that electrical stimulation in one region of the IFG results in activity in other regions, and a high degree of connectivity between the different regions of the IFG has been demonstrated although the functional significance is unknown (Greenlee et al, 2007). It is unclear from the current study why thickness in the pars triangularis had the strongest relationships with neural activity in other parts of the IFG.…”
Section: Discussionmentioning
confidence: 99%